(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The loading on bridges, ports, multi-story parking garages, and airport facilities is typically repeated, so reinforced concrete beams are typically used to support these buildings. Under repeated loads, concrete behaves differently than it does under static stresses. Because of the way the truck is loaded and unloaded, some of the concrete pieces get crushed. This research aims to examine the behavior of reinforced concrete hollow beams subjected to repeated torsion loads. The experimental study involves the evaluation of four reinforced concrete rectangular beams of dimensions (length 3000 mm, height 350 mm, and width 250 mm) with identical reinforcing ratios and tested under pure torsion. There are two beam sections available: solid and hollow. The test program takes into account the influence of hollow shape and load type (monotonic and repeated). On the basis of torque-twist behavior, beam elongation, crack width, behavior and effect of hollow core cracking torque, ultimate torque, and failure mechanisms, test results were discussed. The results of the experiments showed that a circular cavity with a diameter of 10 mm in reinforced concrete beams has a small effect on the properties of reinforced concrete compared with solid-section beams, whether they are subjected to monotonic or repeated torque, with a reduction of the cracking and the ultimate torque of 6.09% and 5.58% for beams subjected to monotonic torque, and with a ratio of 6.6% and 6.03% for beams subjected to repeated torque